Study of engineering cad software in designing / Ayasing Long and Khaizuran Mohd Salleh - Long, Ayasing; Mohd Salleh, Khaizuran
Solid modeling process using integrated software is one of the engineering tools in solving design problems. One of the latest technologies in engineering software application in solid modeling process is by using Pro/E software. In this project, rarely is about the application of Pro/E software in designing a solid modeling mat can be used for further engineering process such as in moulding design, metal stamping, industrial design, CNC machining process and etc. The software that we used is quite similar with other software that already has in the manufacturing marketed nowadays. So in this project, we will try to design a simple product using the Pro/E software and learnt the basic concept in solid modeling. From the obtain result then we will examine the beneficial using the Pro/E software and compare it with the other software